2012
DOI: 10.1002/tox.21831
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos induced testicular damage in rats: Ameliorative effect of glutathione antioxidant

Abstract: This study investigated the induction of oxidative stress in the testes of adult rats exposed to chlorpyrifos (CPF). CPF was administered orally, in a dose of 30 mg/kg body weight to male rats for 90 days, twice weekly. Coadministration of water-soluble nonenzymatic antioxidant glutathione (GSH) was performed in a dose of 100 mg/kg body weight, orally, for the same period. Another two groups of male rats were administered GSH and corn oil, respectively. The activities of superoxide dismutase and GSH reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…In agreement with previous studies, our histopathological examination of the testicular tissue revealed significant decline in the number of spermatogenic cells, Sertoli cells and inter‐tubular blood cells in CPF‐exposed groups (Dutta & Sahu, ; Elsharkawy et al, ; Mandal & Das, ; Mosbah et al, ; Sai et al, ). Among these cells, the mean spermatocyte and spermatid counts were significantly increased by some, and not all, treatment regimens in exercise‐trained groups when compared with the similarly treated sedentary animals (Figure e,f).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies, our histopathological examination of the testicular tissue revealed significant decline in the number of spermatogenic cells, Sertoli cells and inter‐tubular blood cells in CPF‐exposed groups (Dutta & Sahu, ; Elsharkawy et al, ; Mandal & Das, ; Mosbah et al, ; Sai et al, ). Among these cells, the mean spermatocyte and spermatid counts were significantly increased by some, and not all, treatment regimens in exercise‐trained groups when compared with the similarly treated sedentary animals (Figure e,f).…”
Section: Discussionsupporting
confidence: 92%
“…Some previous research works have shown that CPF administration leads to drastic histo‐morphologic changes in the testes of animal models, such as testicular atrophy, shrinkage of the seminiferous tubules, tubular diameter reduction and degenerative changes in the germinal epithelium (Dutta & Sahu, ; Elsharkawy, Yahia, & El‐Nisr, ; Farag et al, ; Mosbah, Yousef, Maranghi, & Mantovani, ). However, other studies have failed to detect some or all of these damages (Joshi et al, ; Kheradmandi, Jorsaraei, Feizi, Moghadamnia, & Neamati, ; Sai et al, ; Wen, Wei, & Pan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, spermatogenesis and sperm function must be protected from oxidative stress. To avoid harmful effects from ROS, the testes mainly use enzymatic copper/zinc superoxide dismutase (Cu/Zn-SOD or SOD1), mitochondrial SOD (Fe/Mn-SOD or SOD2), extracellular SOD (SOD-Ex or SOD3) [Bauche et al 1994;Gu and Hecht 1996;Mruk et al 2002], catalase (CAT) [Dastig et al 2011;Luers et al 2006;Nenicu et al 2007], and selenoenzyme phospholipid hydroperoxide glutathione peroxidase [Baek et al 2007;Kaur et al 2006] and non-enzymatic antioxidants, like reduced glutathione (GSH) [Bilommi et al 2013;Elsharkawy et al 2012]. The cytoplasmic space of sperm is limited and the availability and location of intracellular antioxidant enzymes is restricted, which may be further compromised by the effects of oxidative stress [Weir and Robaire 2007].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Generally, lipid peroxidation (LPO) due to OP poisoning is evidenced by enhanced levels of thiobarbituric acid reactive substances (TBARS) in the plasma, brain, lung, testes, and erythrocytes. [12][13][14][15] The extensive and indiscriminate use of OP pesticides in agriculture has been a major concern because of its potentially known or suspected harmful effects to humans. 4 Moreover, some of these pesticides remain in the soil, ground water, drinking water, marine organisms, and various food products.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Generally, lipid peroxidation (LPO) due to OP poisoning is evidenced by enhanced levels of thiobarbituric acid reactive substances (TBARS) in the plasma, brain, lung, testes, and erythrocytes. 12 15…”
Section: Introductionmentioning
confidence: 99%